IMPLEMENTASI NILAI-NILAI MULTIKULTURAL DI SMAN 2 KEDIRI - Tri Wahyudi Ramdhan (LP2M Universitas Ibrahimy, 2020)
SMAN 2 Kediri is a school that was established in the era of independence which is a condition of historical value and is very adaptive and responsive to the dynamics of plural societies and the development of the education world in Kediri. And in maintaining the diversity that exists, the school has organized education in a democratic and fair and not decriminative manner through a curriculum filled with multicultural values. So as to uncover the application of the curriculum with a load of multicultural values, a study was carried out on the concept of muticultural values that grew and developed in SMA 2 Kediri. This research is a qualitative research with case study research and in data collection using in-depth interviews and observation techniques, as well as documentation. Then the data analysis technique uses interactive techniques from Milles and Huberman. The results showed that the concept of multicultural values implemented in SMA 2 Kediri is a concept of interrelated values and cannot stand alone and grow and develop simultaneously